Immobilized microalgae-driven triboelectric nanogenerators for sustainable bioelectricity production - Kaja, Kushal Ruthvik; Janpum, Chalampol; Komkhum, Tanakit; Hajra, Sugato; Vivekananthan, Venkateswaran; Vittayakorn, Naratip; Thinsurat, Kamon; Ngamcharussrivichai, Chawalit; Kim, Hoe Joon; In-na, Pichaya (My University, 2026)
Triboelectric nanogenerators (TENG) are emerging as promising solutions for decentralised energy generation due to the growing need for sustainable power sources. These devices convert wasted mechanical energy into electricity under ambient conditions, offering advantages such as eco-friendly operation, material versatility, and effective energy scavenging. Despite these benefits, their relatively low electrical output compared to conventional sources like batteries and fuel cells remains a limitation. Microalgae have attracted attention for their ability to produce bioelectricity through photosynthesis and respiration while simultaneously capturing carbon dioxide. Immobilising microalgal cells on conductive substrates improves electron transfer and metabolic activity. In this context, living Chlorella vulgaris TISTR 8580 with varied cell densities was immobilised on aluminium electrodes and incorporated into a TENG platform to explore energy harvesting from solid-solid and solid-liquid interactions. The highest output of 110 V and 330 nA was generated, confirming the microalgae as a promising tribolayer and extending the conventional triboelectric series. However, sustaining cell viability over extended periods remains a challenge, highlighting the need for optimised light and nutrient conditions in future developments.
Keywords: Energy harvesting; Hybrid bioenergy system; Microalgae; Triboelectric nanogenerator